IgG in the control of FcεRI activation: a battle on multiple fronts - Storni, Federico; Vogel, Monique; Bachmann, Martin F.; Engeroff, Paul (Frontiers in Immunology, 2024)
The rising global incidence of IgE-mediated allergic reactions poses a significant challenge to the quality of life of affected individuals and healthcare systems in general, with current treatments being limited in effectiveness, safety, and disease-modifying capabilities. IgE acts by sensitizing the high-affinity IgE receptor FcεRI expressed by mast cells and basophils, tuning these cells for inflammatory degranulation in response to future allergen encounters. In recent years, Immunoglobulin G (IgG) has emerged as an essential negative regulator of IgE-dependent allergic inflammation. Mechanistically, studies have proposed different pathways by which IgG can interfere with the activation of IgE-mediated inflammation. Here, we briefly summarize the major proposed mechanisms of action by which IgG controls the IgE-FcεRI inflammatory axis and how those mechanisms are currently applied as therapeutic interventions for IgE-mediated inflammation.